Stress distribution during cold compression of a quartz aggregate using synchrotron X‐ray diffraction: Observed yielding, damage, and grain crushing. Issue 4 (22nd April 2017) - Cheung, C. S. N.; Weidner, D. J.; Li, L.; Meredith, P. G.; Chen, H.; Whitaker, M. L.; Chen, X.
Abstract: We report new experimental results that quantify the stress distribution within a quartz aggregate during pore collapse and grain crushing. The samples were probed with synchrotron X‐ray diffraction as they were compressed in a multianvil deformation apparatus at room temperature from low pressure (tens of megapascal) to pressures of a few gigapascal. In such a material, stress is likely to concentrate at grain‐to‐grain contacts and vanish where grains are bounded by open porosity. Therefore, internal stress is likely to vary significantly from point to point in such an aggregate, and hence, it is important to understand both the heterogeneity and anisotropy of such variation with respect to the externally applied stress. In our quartz aggregate (grain size of ~4 μm), the measured diffraction peaks broaden asymmetrically at low pressure (tens of megapascal), suggesting that open pores are still a dominant characteristic of grain boundaries. In contrast, a reference sample of novaculite (a highly dense quartz polycrystal, grain size of ~6–9 μm) showed virtually no peak broadening with increasing pressure. In the quartz aggregate, we observed significant deviation in the pressure‐volume curves in the range of P  = 400–600 MPa. We suggest that this marks the onset of grain crushing (generally denoted as P * in the rock mechanic literature), which is commonly reported to occur in sandstones at pressures of this order, in general agreement with a Hertzian analysis of fracturing at grain contacts. Key Points: We observe an event that we associate with collapse that occurs at approximately 400–600 MPa, in agreement with the literature values. In this region, the sample compresses significantly with little increase in pressure At the time of collapse, the differential microscopic stress is approximately 1000 MPa. This value is about an order of magnitude lower than that predicted by a model based on Hertzian fracture mechanics We observe a significant number of grains that remain at zero stress, in both axial and transverse directions, even though the mean stress is significantly high at 5.6 GPa. This indicates that vacant pores persist at least to this pressure